Firenze cattolica e Firenze laica: un confronto pedagogico - Franco Cambi (Firenze University Press, 2018)
The article deals with the pedagogical authors in Florence between nineteen and twentieth centuries, distributed on the Catholic and Laic front. These complex and different contributions have activated significant discussions in the University and in the journals. Florence had been really the capital of Italian culture, also and right in pedagogy.